PEMBATALAN PERKAWINAN AKIBAT WALI NIKAH TIDAK SAH: Analisis Putusan Mahkamah Syar’iyah Banda Aceh Nomor 24/Pdt.G/2020/Ms.Bna - Raihan, Meuthia; Hanapi, Agustin; Amri, Aulil (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
The legal considerations in Decision Number 24/Pdt.G/2020/Ms.Bna do not contain Islamic legal considerations, only referring to the regulations for granting the contents of the posita. This research aims to analyze Decision Number 24/Pdt.G/2020/Ms.Bna in terms of Islamic law which has a verstek decision which grants marriage annulment because the marriage carried out is considered invalid. The research method used is qualitative, namely decision research and literature research using a case approach. After analyzing the decision Number 24/Pdt.G/2020/Ms.Bna, it is relevant to Islamic law. If standard operational procedures at the KUA Baiturrahman District, Banda Aceh City are implemented properly, of course there will be no dispute in this case. The litigants and the community must also be honest and know their lineage well so that no marriage occurs unless it is a marriage approved by Allah Swt.